Effects of Lactobacillus acidophilus on production performance and immunity of broiler chickens and their mechanism - Liu, Jinmei; Gu, Hongxia; Jia, Rui; Li, Shuzhen; Chen, Zhimin; Zheng, Aijuan; Chang, Wenhuan; Liu, Guohua (Frontiers in Veterinary Science, 2025)
IntroductionLactobacillus species have attracted more and more attention as a potential antibiotic substitute for human health and animal production due to their remarkable antibacterial effects. However, the underlying mechanism is unclear. This experiment’s goal was to investigate the impacts of lactic acid bacteria (LAB) on the growth performance, carcass characteristics, immune function of broiler chickens and their mechanism.MethodsOne hundred and eighty 1-day-old AA broilers were used and randomly allocated into 3 treatment groups with 6 replicates of 10 chickens per replicate. The 3 treatment groups were control group (CK), L. acidophilus added group (LAB-E, 1.0 × 108 CFU/kg) for the first 7 days; L. acidophilus added group (LAB-A, 1.0 × 108 CFU/kg) for the whole experimental period. Broilers had free access to water and feed.ResultsThe results showed that addition of L. acidophilus for the whole experimental period significantly decreased ADFI, FCR and the abdominal fat percentage of broilers (p < 0.05), tended to increase the levels of IgG in broiler serum (p = 0.093). The LAB-A group had higher HDL-C content and IL-2, IL-4 content, and lower level of LPS in broiler serum compared to the controls (p < 0.05).DiscussionIn conclusion, L. acidophilus improved feed efficiency and immune function of broilers by controlling nutrient metabolism and inflammation responses of broilers. L. acidophilus can be used as a potential substitute for antibiotics in broiler production.